Arsenic Trioxide Promotes Tumor Progression by Inducing the Formation of PGCCs and Embryonic Hemoglobin in Colon Cancer Cells - Li, Zugui; Zheng, Minying; Zhang, Hao; Yang, Xiaohui; Fan, Linlin; Fu, Fangmei; Fu, Junjie; Niu, Rui; Yan, Man; Zhang, Shiwu (Frontiers in Oncology, 2021)
Arsenic trioxide (ATO) has been used to treat acute promyelocytic leukemia. However, it is not effective in treating solid tumors such as colorectal cancer. We have previously reported that polyploid giant cancer cells (PGCCs) exhibiting the characteristics of cancer stem cells can be generated by various inducers. In this study, ATO was used to induce the formation of PGCCs in LoVo and Hct116 colon cancer cell lines. The migration, invasion, and proliferation abilities of colon cancer cells with and without ATO treatment were assessed by wound-healing, transwell, and plate colony formation assays. The expression of epithelial to mesenchymal transition-related proteins and erythroid differentiation-related proteins in colon cancer cells was further evaluated by western blot and immunocytochemical assays. LoVo and Hct116 cells were transfected with a eukaryotic expression vector for green fluorescent protein (GFP), red fluorescent protein (RFP), H2B-GFP, and H2B-mCherry to study PGCCs formation via cell fusion. WB and ICC assays were performed to assess the expression of cell fusion-related proteins. MG132, small interfering RNA-glial cell missing 1 (GCM1), and chromatin immunoprecipitation-polymerase chain reaction assays were performed to study the role of GCM1/syncytin-1-mediated cell fusion. Clinically, the significance of cell fusion-related proteins and erythroid differentiation-related proteins expression in human colorectal cancer tissues was evaluated. Results of our study showed that ATO induced the formation of PGCCs, and the daughter cells derived from PGCCs gained a mesenchymal phenotype and exhibited strong migration, invasion, and proliferation abilities. PGCCs also produced embryonic hemoglobin-delta and -zeta with strong oxygen-binding ability and erythroid differentiation-related proteins after ATO treatment. In addition, cell fusion was observed during the formation of PGCCs, indicated by the presence of yellow fluorescence via the GCM1/syncytin-1 signaling pathway. Clinically, the expression of cell fusion-related and erythroid differentiation-related proteins gradually increased with the progression of human colorectal cancer tissues. In conclusion, ATO can promote tumor progression by inducing the formation of PGCCs via GCM1/syncytin-1-mediated cell fusion. PGCCs can produce daughter cells with high invasion and migration abilities and embryonic hemoglobin with strong oxygen binding ability, promoting survival of tumor cells in a hypoxic microenvironment.